STUDI TENTANG PARTISIPASI DAN PERSEPSI SISWA TERHADAP PEMBELAJARAN SENI BUDAYA SUB BIDANG STUDI SENI RUPA DI SMPN 4 LEMBAH GUMANTI - RAMDA FATRIA, Dr. Ramalis Hakim, M.Pd., Dra. Ernis, M.Pd. (Universitas Negeri Padang, 2018)
This thesis examines how student participation and perception in learning in school. As still found the problem of lack of student participation in the task and the lack of participation in bringing materials for the task of art subjects, as well as the perception of some students who consider that the subjects of art is not too important than other subjects.The purpose of this thesis is to find out how the participation and perception of students in art learning. This research method using quantitative research type, with data collection method through research questionnaire, in data processing researcher using SPSS version 16 application.The results of research conducted at SMPN 4 Lembah Gumanti to the participation and perceptions of students in art learning have good participation and good perception.Keywords: partispasi, perception, art learning.